Near-band-edge exciton polarization change in ZnO nanowires. Issue 2 (24th November 2014) - Zeng, Zaiping; Petoni, Alexia; Garoufalis, Christos S.; Baskoutas, Sotirios; Bester, Gabriel
Abstract : Exciton polarization change in ultrathin ZnO nanowires. Abstract : Using the atomistic pseudopotential method complemented by configuration interaction calculations, we have studied the electronic and optical properties of ZnO nanowires (NWs) in the presence of quantum confinement effects. Our results indicate that the near-band-edge exciton experiences a crossover from an in-plane polarized A-exciton (for D ≥ 3 nm) to an out-of-plane polarized C-exciton (for D < 3 nm) due to quantum confinement. This transition leads to a non-monotonic variation of Stokes shift, exhibiting a maximum value around the critical diameter of 3 nm. The observed behavior is analyzed by a stepwise inclusion of correlation effects, leading to a comprehensive description of the excitonic fine structure.